Cystoscopy to investigate the prevalence of prostatic utricle cyst in boys with proximal hypospadias and its implications in medium-term follow-up - Wong, Yuenshan Sammi; Tam, Yuk Him (Frontiers in Pediatrics, 2025)
PurposeProstatic utricle cyst (PUC) is known to be associated with hypospadias. We aimed to investigate the prevalence of PUC in children with proximal hypospadias by cystoscopy, and risk of symptom development after hypospadias repair.MethodsWe retrospectively reviewed the records of patients who underwent 2-stage repair for proximal hypospadias and had cystoscopy for PUC assessment over the period of January 2017–September 2022.ResultsA total of 34 patients with penoscrotal, scrotal or perineal hypospadias were included for review. First-stage repair was performed at a median age of 12 months. The median ventral curvature was 70 degrees (range 45–90). 4 patients had differences of sex development including 45,X/46,XY mosaicism (n = 2) and 46,XY partial gonadal dysgenesis (n = 2). PUC was detected by cystoscopy in 25/34(73.5%) patients, with longitudinal dimensions 10–35 mm (median = 15 mm). At a mean follow-up of 30 months after hypospadias repair, 3/25(12%) patients developed symptoms associated with PUC including recurrent epididymoorchitis (n = 1), post-void dribbling (n = 1) and pyuria (n = 1). 3/10 PUC ≥20 mm became symptomatic compared with none of PUC <20 mm (p = 0.024). The patient with recurrent epididymoorchitis eventually underwent definitive surgery of PUC excision by robot-assisted approach.ConclusionsPUC is highly prevalent in proximal hypospadias. The use of the smallest-sized cystoscope as a screening tool can increase the diagnostic yield. Integrating cystoscopy in hypospadias surgery for concurrent PUC assessment can be considered as an option for patients with proximal hypospadias. Although the vast majority of PUC remains asymptomatic, those ≥20 mm in longitudinal dimensions may be associated with an increased risk of subsequent symptom development.